COMPREHENSIVE REVIEW ON EXPLORING THE ROLE OF ARTIFICIAL INTELLIGENCE IN REVOLUTIONIZING MEDICAL DECISION-MAKING. - 1Mohammed Hamad Hadi Alyami, 2Ali Saleh Bin Abdullah Almunyif, 3Mohammed Nattash Saleh Alzamanan, 4Mahdi Saleh M Alrabeai, 5Mana Mohammed M Alrabiey, 6Ali Mohammed H Alrrabeai, 7Ali Hamad Ali Alkulayb, 8Saeed Mohammed Ali Alghubari (Chelonian Research Foundation, 2023)
Artificial intelligence (AI) has gotten to be a capable driver of changing the worldwide economy, but healthcare is especially vital. This survey portrays the advancement of artificial intelligence in clinical decision-making and surveys current writing to assess current applications, strategies, and results. The effects of artificial intelligence convey reality, treatment planning, determination, and personalized medication. AI employs machine learning (ML) and profound learning (DL) to analyze huge sums of vital information, including clinical study electronic wellbeing records (EHR), genomics, and substantial archives. The effect is significant, with AI-powered frameworks performing comparable to or superior to those of human specialists. Be that as it may, challenges such as information security issues, algorithmic inclinations, and administrative systems still exist. In the future, collaborative endeavours and viable execution forms will be required to guarantee the dependable integration of AI into healthcare. Understanding these problems will open the total potential of artificial intelligence and usher in an unused time of self-determination, personalization, and data-driven healthcare. Keywords: artificial intelligence, Healthcare, Medical Decision-Making, Machine Learning, Deep Learning